The Conceptual Design of a Variable Camber Wing - Spencer Troy P. Cortez; Seksan Winyangkul; Suwin Sleesongsom (My University, 2025)
The variable camber wing (VCW) is a morphing wing design anticipated to enhance unmanned aerial vehicles’ (UAVs’) performance in flight through continuously changing shape. The performance of VCWs has been proven, but techniques for their integration, including aerodynamic analysis, mechanism synthesis, and structural tests, still lag in development at the conceptual design stage. Therefore, this research focuses on designing a variable camber wing, a key area for the advancement of morphing aircraft. Inspired by the high-lift capabilities of traditional aircraft devices but aiming for smoother airflow through continuous shape alteration, this research proposes a novel three-step design for a structurally integrated VCW. This approach begins with a critical aerodynamic analysis to determine wing shape adaptations across various flight conditions, followed by a mechanism synthesis phase to design a four-bar linkage that accurately approximates the desired trailing edge deflections by utilizing a variant of teaching–learning-based optimization. The objective is to minimize error between the intended and actual coupler link while adhering to design constraints for proper integration in the wing structure. Finally, structural analysis evaluates the skin’s ability to withstand operational loads and ensure the integrity of the VCW system. The design result demonstrates the success of this three-step approach to synthesizing a VCW mechanism that meets the defined aerodynamic (actual deflection of 9.1764°) and structural targets (maximum Von Mises stress of 81.5 MPa and maximum deflection of 0.073 m), paving the way for enhanced aircraft performance.
Keywords: Camber (aerodynamics); Conceptual design; Advanced Aircraft Design and Technologies